An audit of Ninewells Hospital fertility preservation service. (4th July 2018) - Chatterton, Fiona; Kay, Vanessa
Abstract: Background: Infertility is a devastating consequence of some medical and surgical interventions. Men can protect their fertility by storing or 'banking' sperm before beginning treatment. This is called fertility preservation. Fertility preservation is traditionally offered to cancer patients undergoing gonadotoxic therapy. Aims: This study reports the results of an audit of the Ninewells Hospital fertility preservation service. It aims to characterise the patients who attended our service and assess their utilisation rate and outcome of treatment. Method: A retrospective study carried out between January 2000 and March 2017. Data was collected using a combination of laboratory and clinical records. Results: A total of 296 patients attended for fertility preservation, of which 264 banked sperm. The number of men referred for sperm banking increased during the study period from 3 in 2000 to 26 in 2016. Testicular cancer (41.7%) was the most common indication followed by, haematological malignancies (33.0%), other malignancies (15.2%) and benign disease (10.2%). The proportion of men with benign disease increased over-time and accounted for 15% of all patients since 2015. At the time of sperm banking, the median age was 29.8 years. Fourteen men (5.3%) returned for fertility treatment with their banked sperm after an average of 40.8 months. After a total of 32 treatment cycles, 12 babies were born (6 singletons and 3 twins). Eight of the fourteen couples succeeded in having at least one child (57.1%). A small proportion of men engaged in fertility monitoring (9.5%) or disposed of their banked sperm (5.7%). Conclusions: There is an increasing demand for fertility preservation, especially from patients with benign disease. Only a small proportion of men utilised their banked sperm, however, those that did had a good chance of becoming fathers. Data from this study will be used to review our referral pathways and inform our future practice.